Distal Extension of the Direct Anterior Approach to the Hip Poses Risk to Neurovascular Structures: An Anatomical Study. (21st January 2015) - Grob, Karl; Monahan, Rebecca; Gilbey, Helen; Yap, Francis; Filgueira, Luis; Kuster, Markus
Abstract : Background: The anterior approach to the hip gained popularity for total hip arthroplasty in recent years. Distal extension of the anterior approach, sometimes needed intraoperatively, potentially endangers neurovascular structures to the quadriceps. The aim of this study was to determine the anatomical structures placed at risk by distal extension of the anterior approach to the hip. Methods: Seventeen cadaveric hemipelves from twelve human specimens were dissected. The femoral nerve and its branches and the vessels arising from the lateral femoral circumflex artery were assessed in relation to the distal extension of the anterior approach. The damage caused by the introduction of a cerclage cable passer was also investigated. Results: The area immediately distal to the intertrochanteric line is a common entry point for several nerve branches and is a useful distal landmark for surgeons to use to protect important neurovascular structures. The distal extension of the anterior approach compromises the nerve supply to the anterolateral portions of the quadriceps. Introduction of a cerclage cable passer through the anterior access also jeopardizes nerve branches to the vastus lateralis, lateral parts of the vastus intermedius, and branches of the lateral femoral circumflex artery. Conclusions: Distal extension of the direct anterior approach to the hip is challenging to accomplish without neurovascular injury to anterolateral parts of the quadriceps muscle group. In addition, important neurovascular structures are endangered with the introduction of a cable passer through the anterior approach. Clinical Relevance: Distal extension of the direct anterior approach to the hip beyond the intertrochanteric line may compromise neurovascular structures supplying the quadriceps muscle.